2020
DOI: 10.22541/au.158999387.76467979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probiotics in viral infections, with a focus on COVID-19: A Systematic Review

Abstract: Aim: COVID-19, a newly discovered virus disease, can be affected by probiotics. So, we tried to review the possible effects and associations of probiotics on viral infections focusing on SARS-CoV-2. Methods: We searched on PubMed, EMBASE, Google Scholar, Science Direct, Scopus and Web of Science up to May 2020 to identify interventional & observational studies documenting the effects of probiotics strains on interleukins, virus titres, and antibody production with a focus on confirmed diagnosis of SARS-CoV-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
8
0
2
Order By: Relevance
“…Penderita COVID-19 dapat mengalami disbiosis yang ditandai dengan menurunnya Lactobacillus dan Bifidobacterium, di samping juga akibat penggunaan antibiotik yang sering menyebabkan antibiotic-associated diarrhea. 18 Belum banyak studi atau penelitian yang menjelaskan efektivitas penggunaan probiotik dalam mengatasi infeksi COVID-19. Sebagian besar bukti penelitian efek probiotik dilakukan pada virus-virus influenza yang bukan merupakan strain virus SARS CoV-2.…”
Section: Peran Probiotik Sebagai Antiinflamasi Pada Infeksi Covid-19unclassified
“…Penderita COVID-19 dapat mengalami disbiosis yang ditandai dengan menurunnya Lactobacillus dan Bifidobacterium, di samping juga akibat penggunaan antibiotik yang sering menyebabkan antibiotic-associated diarrhea. 18 Belum banyak studi atau penelitian yang menjelaskan efektivitas penggunaan probiotik dalam mengatasi infeksi COVID-19. Sebagian besar bukti penelitian efek probiotik dilakukan pada virus-virus influenza yang bukan merupakan strain virus SARS CoV-2.…”
Section: Peran Probiotik Sebagai Antiinflamasi Pada Infeksi Covid-19unclassified
“…A COVID-19 patient with multiple complications reported a favourable outcome after administration of probiotics, including Lactobacillus acidophilus, Bifidobacterium and Saccharomyces boulardii, along with vitamins & minerals [6]. Similarly, a 9 years old boy diagnosed with COVID 19 exhibited disappearance of mild diarrhoea symptoms when administered probiotics [6].…”
Section: Letter To the Editormentioning
confidence: 99%
“…A COVID-19 patient with multiple complications reported a favourable outcome after administration of probiotics, including Lactobacillus acidophilus, Bifidobacterium and Saccharomyces boulardii, along with vitamins & minerals [6]. Similarly, a 9 years old boy diagnosed with COVID 19 exhibited disappearance of mild diarrhoea symptoms when administered probiotics [6]. The usefulness of probiotics in the treatment and prevention of viral infections are clear, due to their proven immunomodulatory activity and ability to stimulate interferon production [6].…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The currently available probiotics are mostly bacteria such as Lactobacillus, Bifidobacterium, Saccharomyces, Enterococcus, Leuconostoc, and Bacillus (Akter & Rabeta, 2021;Hill et al, 2014). Among all lactobacilli species, several members operating in the gastrointestinal tract and nasal-pharynx have a good anti-corona viral activity (Pourhossein & Moravejolahkami, 2020). On contrary to bacteria, despite their significance and distribution in foods, a research gap was found in the study of probiotic potential from yeasts (Chen et al, 2010).…”
mentioning
confidence: 99%